BARRIER ANALYSIS AND STRATEGY DEVELOPMENT FOR IMPLEMENTATION OF SMART SUPPLY CHAIN MANAGEMENT IN INDONESIAâS ELECTRONICS INDUSTRY - Kurrita Aini, Briliana
The electronics industry, one of a priority sector in Indonesia, shows a positive grew in the recent year. However, it faces major challenges due to lack of an integrated supply chain, prompting its inclusion in the Ministry of Industry's Strategic Planning to enhance local industry competitiveness. Despite efforts, Indonesia faces ongoing challenges with logistics and supply chain efficiency due to poor infrastructure, unreliable IT networks, and high logistics costs. Smart supply chain management (SCM 4.0) uses advanced technologies like IoT, AI, and big data to enhance decision-making, improve operational efficiency, and increase supply chain visibility and agility. Despite its complexities, SCM 4.0 has the potential to boost the quality of the electronics industry's supply chain in Indonesia and support the national economy. However, successful implementation requires addressing the barriers to ensure the successful implementation. This study attempts to identify the barriers of smart supply chain management in Indonesia’s electronics industry and found the hierarchical relationship among them. Systematic Literature Review used to finds the initial barriers related to the implementation of smart supply chain management which resulting the total of 21 initial barriers. The initial barriers then validated using Delphi method and resulting in only 12 barriers considers essentials to be analyzed in the next step. ISM-MICMAC has been utilized to build the hierarchical relationship among the barriers and grouping them based on their driving and dependence power. Lack of government regulation and supports and also lack of government incentives become the most fundamental barriers and also categorized as independent barriers. Based on the results, this study also proposed the smart supply chain management implementation strategy for Indonesia’s electronics industry.